2020
DOI: 10.1007/s00421-020-04366-w
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-respiratory, oxidative stress and acute mountain sickness responses to normobaric and hypobaric hypoxia in prematurely born adults

Abstract: Purpose We compared the effects of hypobaric and normobaric hypoxia on select cardio-respiratory responses, oxidative stress and acute mountain sickness (AMS) severity in prematurely born individuals, known to exhibit blunted hypoxic ventilatory response. Methods Sixteen prematurely born but otherwise healthy males underwent two 8-h hypoxic exposures under: (1) hypobaric hypoxic [HH; terrestrial altitude 3840 m; P i O 2 :90.2 (0.5) mmHg; BP: 478 (2) mmHg] and (2) normobaric hypoxic [NH; P i O 2 :90.6 (0.9) mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our study confirmed a higher oxygen saturation in NH vs. HH after 24 h of hypoxic exposure. This is already well described for shorter exposition times ( Aebi et al, 2020 ; Debevec et al, 2020 ) and logically was also already reported in the three support experiments of the present study. However, the latter was still debated for exposures longer than 8 h ( Coppel et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed a higher oxygen saturation in NH vs. HH after 24 h of hypoxic exposure. This is already well described for shorter exposition times ( Aebi et al, 2020 ; Debevec et al, 2020 ) and logically was also already reported in the three support experiments of the present study. However, the latter was still debated for exposures longer than 8 h ( Coppel et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, recent research suggested that NH and HH are not interchangeable (Fulco et al, 2011;Millet et al, 2012;Saugy et al, 2014Saugy et al, , 2016aCoppel et al, 2015;DiPasquale et al, 2015a;Conkin, 2016) although the differences between HH and NH are still debated (Millet and Debevec, 2020;Richalet, 2020). The following differences were already reported for a matched inspired oxygen pressure (P I O 2 ) in HH vs. NH, respectively: (1) lower pulse oximeter oxygen saturation (S p O 2 ) (Saugy et al, 2016c;Aebi et al, 2020;Debevec et al, 2020); (2) greater performance impairment (Beidleman et al, 2014;Saugy et al, 2016a), both recently confirmed in a study with perfectly controlled environmental factors (Takezawa et al, 2021); (3) higher oxidative stress (Faiss et al, 2013;Ribon et al, 2016); (4) impaired nitric oxide bioavailability (Faiss et al, 2013); (5) greater fluid retention (Loeppky et al, 2005;Conkin and Wessel, 2008), and (6) sleep structure perturbation (Heinzer et al, 2016;Saugy et al, 2016b). In addition, breathing patterns are affected as well: lower tidal volume, lower minute ventilation, higher physiological dead space, and higher respiratory frequency during HH exposure compared to NH (Savourey et al, 2003;Conkin and Wessel, 2008;Saugy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study by Irarrázaval et al [ 41 ] showed glutathione peroxidase (GPx) activity decreased under hypobaric hypoxia conditions; this study emphasized the relationship between oxidative stress and AMS severity. Moreover, adults who had been born prematurely and were later exposed to hypobaric hypoxia (3840 m; 8 h) showed a decrease in antioxidant capacity and an increase in AMS severity [ 42 ].…”
Section: Oxidative Stress and High-altitude Diseasesmentioning
confidence: 99%
“…With regard to hypoxia-induced changes in [HCO 3 − ] after several hours of altitude exposure, the kidney responds to a decline in PCO 2 and an increase in pH b through excretion of HCO 3 − known as compensation of respiratory alkalosis. According to the literature, we expected a reduction in [HCO 3 − ] by 1.8 ± 2.5 mmol/L and an [HCO 3 − ] of 21.7 ± 2.5 mmol/L for acute 12-h exposure to an altitude of 3,000 m 5 , regardless of a normobaric or hypobaric acute hypoxic exposure 43 , 44 . However, in Study A, after 12 h of hypoxic exposure, there was a significant reduction in [HCO 3 − ] of only 1.4 ± 0.3 mmol/L and [HCO 3 − ] was 23.3 ± 1.3 mmol/L.…”
Section: Discussionmentioning
confidence: 92%